PENERJEMAHAN DIALOG BERIMPLIKATUR DARI BAHASA INGGRIS KE BAHASA INDONESIA DALAM NOVEL A GAME OF THRONES - Lia Nurmalia Nurmalia (Wanastra: Jurnal Bahasa dan Sastra, 2017)
Abstract  –  The objectives of this research are to know the types of implicature contained in the dialogue of A Game of Thrones, the strategy of translation used by the translator in translating the dialogue consisting implicature, and the equivalence deviation of translation. This research uses  qualitative method which is comparative content analysis. The data is the dialog taken from A Game of Thrones. All the dialogues in the source text and in the target text are analyzed by using the comparative model. To analyze the types of implicature used Desilla’s Theory. To analyze the strategy of translation used Molena and Albir and Newmark’s theories. To analyze the equivalence used Koller’s theory, and to analyze the deviation in translation used Newmark’s theory. The risult of this research shows there are three types of implicature transference in translation. They are presevation about 129 (96.3%), explicitation 2 (1.5%), and modification 3 (2.3%). It means most of implicature in the dialogues are transfered into the equivalent implicature. For strategy of translation,  there are eleven strategies of translation used by the translator. They are transposition 50 (26.3%), transference 11 (6%), modulation 37 (19.4%), cultural equivalence 16 (8.4%), addition 7 (3.6%), reduction 12 (6.3%), literal translation 34 (18%), explicitation 13 (6.8%), implicitation 8 (4.2%), calque 1 (0.5%), and paraphrasing 1 (0.5%). For equivalence can be concluded that the most of the dialogue reaches the equivalence. The equivalence of konotative 37 (28%), denotative 38 (28.8%), normatif text 2 (1.5%), pragmatic 22 (16.7%), and formal 33 (25%). For the deviation in translation there are three types deviation. The first is the deviation caused by the grammatical differences 2 dialogues. The second is the deviation caused by modulation 1 dialogue, and the third is the deviation caused by reduction 1 dialogue.    Key Word: Translation, implicature, equivalence